Enterprising places leadership and governance networks - Pugalis, Lee; Liddle, Joyce, 1952- (Emerald, 2014)
Mobilising an enterprise surge in specific places has become the leitmotif of contemporary spatial interventions and state-sponsored strategies. Global economic shocks, rising demands for welfare services and public sector austerity measures are signifiers of the complex processes that have heightened public policy imperatives associated with enabling enterprise. Consequently, the search for entrepreneurial synergies has intensified the need for devising mechanisms for delivering broader social, cultural, environmental, economic and political objectives. However, developing collaborative leadership necessary to mobilise diverse networks of actors that can implement strategies sensitive to the plurality of place is not a straightforward task: negotiating the generation of entrepreneurial synergies in places calls for alternative conceptual tools, and complementary policies. Using theoretical explanations and empirical analysis, the chapters critically examine the entrepreneurial turn of public policy and urban studies.
Keywords: Entrepreneurship.; elektronické knihy; electronic books